Plan de comunicación estratégica para fortalecer la imagen de la Secretaría Nacional de la Administración Pública-SNAP como institución rectora de la eficiencia en la gestión pública - Villena Fuentes, Ximena Alexandra (2015)
The National Secretariat of Public Administration is a public institution, rector of politics and strategies of efficiency and quality of public services. These competencies were assigned under legislation and presidential decrees, and to his management were separated from the Presidency of the Republic in 2013. It was felt that exists among key audiences of the National Secretariat of Public Administration dispersed perception about the competence of this entity, being necessary to position it as a leading institution in matters of governance, strategically communicating their actions to achieve quality, innovation and simplification of procedures in public services...